2012
DOI: 10.1111/j.1365-2133.2011.10745.x
|View full text |Cite
|
Sign up to set email alerts
|

Pachyonychia congenita patients with mutations in KRT6A have more extensive disease compared with patients who have mutations in KRT16

Abstract: Phenotypic differences between patients with KRT6A and KRT16 mutations support adoption of a new classification system based on the mutant gene (PC-6a, PC-16) rather than the PC-1 nomenclature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…Symptomatic mucosal involvement with leukokeratosis of the mouth and upper airways, as well as the larynx, is an important clinical feature of PC. It appears to be more pronounced in KRT6A mutation carriers . Oral leukokeratosis is frequently seen in PC and can be one of the earliest signs of disease.…”
Section: Summary Of Identified Mutations and Associated Mucosal Manifmentioning
confidence: 97%
See 1 more Smart Citation
“…Symptomatic mucosal involvement with leukokeratosis of the mouth and upper airways, as well as the larynx, is an important clinical feature of PC. It appears to be more pronounced in KRT6A mutation carriers . Oral leukokeratosis is frequently seen in PC and can be one of the earliest signs of disease.…”
Section: Summary Of Identified Mutations and Associated Mucosal Manifmentioning
confidence: 97%
“…Laryngeal involvement is a less common feature. It might be asymptomatic but usually presents as hoarseness, stridor and, occasionally, as a life‐threatening respiratory distress . To date, few case reports of laryngeal involvement in patients with PC exist in the literature …”
Section: Summary Of Identified Mutations and Associated Mucosal Manifmentioning
confidence: 99%
“…Phenotypic overlap among PC genotypes has been observed, and none of the clinical features described is specific to a particular gene . However, patients with mutations in KRT6A, like our patient, tend to have more extensive disease and will most likely present oral leukokeratosis …”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, a large-scale phenotypic and molecular study of the disease has revealed that despite the name of the syndrome, nail involvement is not universal in PC [1]. In contrast, palmoplantar involvement is universally found in adult PC patients whose diagnosis has been confirmed at the molecular level [1,5]. In fact, some patients solely manifest thickening of the plantar skin surface, which may under certain circumstances lead to confusion with other forms of hereditary palmoplantar keratoderma [6].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some patients solely manifest thickening of the plantar skin surface, which may under certain circumstances lead to confusion with other forms of hereditary palmoplantar keratoderma [6]. A very typical feature of plantar hyperkeratosis in PC patients is the existence of severely debilitating pain, confining many patients to wheelchairs from childhood [1,5,6]. The reported severity of plantar pain often bears little correlation to the extent of the callus, what could indicate that factors other than pressure from the callus itself may contribute to the pain [1,7].…”
Section: Introductionmentioning
confidence: 99%